Educational Needs of Health Care Providers Working in Long-Term Care Facilities with Regard to Pain Management - Yannick Tousignant-Laflamme; Michel Tousignant; David Lussier; Paule Lebel; Maryse Savoie; Lyne Lalonde; Manon Choinière (Pain Research and Management)
BACKGROUND: The prevalence of chronic pain ranges from 40% to 80% in long-term care facilities (LTCF), with the highest proportion being found among older adults and residents with dementia. Unfortunately, pain in older adults is underdiagnosed, undertreated, inadequately treated or not treated at all. A solution to this problem would be to provide effective and innovative interdisciplinary continuing education to health care providers (HCPs).